Finding RB/Rpi-blb1/Rpi-sto1-like sequences in conventionally bred potato varieties - O. Y. Antonova; N. S. Klimenko; Z. Z. Evdokimova; L. I. Kostina; T. A. Gavrilenko (Вавиловский журнал генетики и селекции)
The main objectives in potato breeding are increasing yield abilities and improving resistance to numerous pathogens and pests. Among them, the late blight caused by the Phytophthora infestans oomycete is one of the most destructive potato diseases both in Russia and worldwide. Wild relatives of cultivated potato are traditionally used in breeding as the source of valuable R genes conferring resistance to pathogens. Of particular interest are Mexican wild species because Mexico is the centre of origin and diversity of P. infestans and at the same time, it is the centre of potato species diversity.  Mexican wild potato species S. bulbocastanum and S. stoloniferum are an important source of the R genes conferring broad-spec trum resistance against various isolates of P. infestans (Rpi-blb1,  Rpi-blb2, Rpi-sto1). Recently these genes have been transferred into cultivated potato gene pool using the cisgene  approach. At the same time there is a high probability of finding geno types with the Rpi-sto1 gene (functional homologues of  Rpi-blb1) among conventionally bred varieties because for about 40 years S. stoloniferum has been used in breeding as a source of the Rysto and Ry-fsto genes of the extreme resistance to the most important viral pathogen PVY. In this study 188 potato varieties bred in Russia and in near-abroad countries were screened for the presence of six gene-specific markers of the RB/Rpi-blb1 =  Rpi-sto1 and Rpi-blb2 genes conferring broad-spectrum resistance against P. infestans, and for the markers linked to the Rysto and Ry-fsto genes conferring extreme resistance to PVY. In addition, a marker for detecting male sterile mitochondrial DNA type gamma derived from S. stoloniferum was used. The genotypes selected through the molecular markers were divided into four groups: (A) 13 PVY resistant varieties carrying diagnostic markers of the Rysto, Ry-fsto genes and having sterile mt-type gamma; (B) four varieties possessing mt-type gamma and not having the markers of the R genes introgressed from S. stoloniferum; (C) eight genotypes carrying five gene-specific markers for the RB/Rpi-blb1/= Rpi-sto1; (D) the rest 166 (86.9 %) varieties not possessing any of the diagnostic markers associated with the S. stoloniferum genetic material. The sequences of the Rpi-sto1- and BLB1 F/R-amplicons were identical in all the genotypes of group ‘C’ and showed respective 99 % and 100 % similarity to the corresponding fragments of the Rpi-sto1 and Rpi-blb1 genes from the GenBank database. Among the genotypes of group ‘C’ various mt-types were detected, and some of them were male fertile.